Rancang Bangun Mesin Perajang Singkong yang Memenuhi Aspek Ergonomis untuk Meningkatkan Produktivitas Pekerja - Putri Rachmawati (Proklamasi 45 University, 2019)
Micro, Small and Medium Enterprises, which are often referred to as SMEs in the field of food processing in Yogyakarta, are numerous one of which is the cassava processing SMEs in Gunungkidul Regency. Cassava is an agricultural commodity that is a typical local product of Special District of Yogyakarta, especially in Gunungkidul Regency. SMEs are proven as a support of the national economy during the global economic crisis, for that it must be considered and developed thoughtfully. Workers at cassava processing SMEs often experience several complaints. This study aims to analyze the claims and needs of workers in cassava processing SMEs, then made a cassava chopper redesign tool that meets the ergonomic aspects and increases the productivity of these cassava processing SMEs. Analysis of worker complaints is done by distributing questionnaires about the comfort level of the work process. It is subsequently translated into the redesign of cassava chopper tools in the form of computer design drawings. After that, the process of making the redesign of machines and testing productivity. The driving motor used is an electric motor 1 PK. Based on the analysis of complaints and the needs of workers in cassava processing SMEs, it was found that the correlation between the needs of workers and the value of technical characteristics with the results obtained was 73.95. While the results of experiments that have been carried out on cassava chopper machines that have been carried out in redesign and construction that meet ergonomic aspects or comfort levels have a productivity level of 40 kgs/hour.